Confluence and contours: reflexive management of environmental risk - Soane, Emma; Schubert, Iljana; Pollard, Simon J. T.; Rocks, Sophie A.; Black, Edgar (Wiley, 2015)
Government institutions have responsibilities to distribute risk management funds meaningfully and to be accountable for their choices. We took a macro-level sociological approach to understanding the role of government in managing environmental risks, and insights from micro-level psychology to examine individual-level risk-related perceptions and beliefs. Survey data from 2,068 U.K. citizens showed that lay people's funding preferences were associated positively with beliefs about responsibility and trust, yet associations with perception varied depending on risk type. Moreover, there were risk-specific differences in the funding preferences of the lay sample and 29 policymakers. A laboratory-based study of 109 participants examined funding allocation in more detail through iterative presentation of expert information. Quantitative and qualitative data revealed a meso-level framework comprising three types of decisionmakers who varied in their willingness to change funding allocation preferences following expert information: adaptors, responders, and resistors. This research highlights the relevance of integrated theoretical approaches to understanding the policy process, and the benefits of reflexive dialogue to managing environmental risks.
Keywords: Agency; Decision making; Environmental risk; Government funding; Policy